Postoperative Aseptic Intracranial Granuloma: The Possible Influence of Fluid Hemostatics - Mario Ganau; Nicola Nicassio; Leonello Tacconi (Case Reports in Surgery)
Background. Numerous reports have demonstrated how postoperative intracranial granulomas can often mimic neoplasm clinically, radiologically, and even macroscopically. Herein we present an unusual case of postsurgical intracranial aseptic granuloma secondary to a chronic inflammatory reaction without any identifiable retained foreign body. Case Description. A 71-year-old patient started complaining of severe headache seven months after surgical excision of WHO Grade I right frontal falx meningioma. CT and MRI scans disclosed a contrast-enhanced lesion with diffuse mass effect in the previous surgical site. The lesion was resected; intraoperative finding and histological specimens led to the diagnosis of postoperative granuloma, likely expression of a glial reaction to the fluid absorbable hemostatics applied in the surgical site after meningioma excision. The possible granuloma-inducing materials and the timing of granuloma formation are discussed. Conclusion. A comprehensive analysis of clinical and neuroradiological data, as well as results of blood tests including positive and negative acute phase proteins, is mandatory to raise the suspicion of postoperative granuloma. The treatment options should be evaluated on a case-by-case basis, with a conservative attitude being the one of choice only for patients without progressive neurological deficit. Alternatively, aggressive surgical treatment and histopathological examination should be advocated.